Investigations on Piper betle grown in Sri Lanka - L. S. R., Arambewela; L. D. A. M., Arawwawala; K. G, Kumaratunga; D. S, Dissanayake; W. D., Ratnasooriya; S. P., Kumarasingha (Pharmacognosy Reviews, 2011)
Piper betle is an economically important plant cultivated in Sri Lanka. Although more than 12 cultivars of betel are reported in Sri Lanka, very few scientific investigations have been carried out on them. Studies on the chemical constituents indicated that safrole is the major constituent, followed by chavibitol acetate, in the essential oil of common betel leaves of Sri Lanka. Investigations on the bioactivities of P. betle revealed the presence of antimicrobial, insecticidal, antioxidant, antinociceptive, antidiabetic and gastroprotective activities. In addition, P. betle was found to be safe in terms of hepatotoxicity, renotoxicity, hematotoxicity, gross morphology, weights of organs, stress or aversive behaviors in rats. The above fi ndings indicate the vast potential of P. betle yet to be harnessed for the benefit of mankind and the betel industry of Sri Lanka.
Keywords: Anatomy; bioactivities; chemical constituents; morphology; Piper betle; safety profile